'With a little help from my friends': exploring mutual engagement and authenticity within foodie influencers' communities of practice. Issue 13 (2nd September 2022) - Miguel, Cristina; Clare, Carl; Ashworth, Catherine J.; Hoang, Dong
ABSTRACT: The aim of this paper is to analyze the dynamics of mutual engagement within the foodie influencer communities of practice created via Instagram. The study is based on 20 in-depth interviews with foodie Instagrammers. Findings demonstrate that unlike other communities of practice, rather than competing among themselves, foodies learn from each other, exchange tips, help those starting out in the field and attend events together. Close collaboration also leads to the formation of strong friendship bonds. However, findings show that whilst authenticity of content is deemed important, elements of influencer engagement are artificially orchestrated within their own community of practice. These findings have implications for marketing professionals in terms of evaluating influencersʻ engagement authenticity and the selection criteria they consider with regard to targeting appropriate and specific influencers to work with.